Identification of RAPD markers linked to A and B genome sequences in Musa L - Pillay, M.; Nwakanma, D.; Tenkouano, A. (Canadian Science Publishing, 2000)
Plantains and bananas (Musa spp. sect. eumusa) originated from intra- and interspecific hybridization between two wild diploid species, M. acuminata Colla. and M. balbisiana Colla., which contributed the A and B genomes, respectively. Polyploidy and hybridization have given rise to a number of diploid, triploid, and tetraploid clones with different permutations of the A and B genomes. Thus, dessert and highland bananas are classified mainly as AAA, plantains are AAB, and cooking bananas are ABB. Classification of Musa into genomic groups has been based on morphological characteristics. This study aimed to identify RAPD (random amplified polymorphic DNA) markers for the A and B genomes. Eighty 10-mer Operon primers were used to amplify DNA from M. acuminata subsp. burmannicoides clone 'Calcutta 4' (AA genomes) and M. balbisiana clone 'Honduras' (BB genomes). Three primers (A17, A18, and D10) that produced unique genome-specific fragments in the two species were identified. These primers were tested in a sample of 40 genotypes representing various genome combinations. The RAPD markers were able to elucidate the genome composition of all the genotypes. The results showed that RAPD analysis can provide a quick and reliable system for genome identification in Musa that could facilitate genome characterization and manipulations in breeding lines.Key words: banana and plantain, A and B genomes, genomic groups, RAPD markers.